2014
DOI: 10.1074/jbc.m113.512913
|View full text |Cite
|
Sign up to set email alerts
|

Deleted in Breast Cancer 1 (DBC1) Protein Regulates Hepatic Gluconeogenesis

Abstract: Background: Gluconeogenesis is an important physiological pathway in response to fasting and stress. Results: DBC1 regulates gluconeogenesis and PEPCK expression by a mechanism that is at least in part explained by the Rev-erb␣ and the deacetylase SIRT1. Conclusion: A new role for DBC1as a regulator of PEPCK expression is described. Significance: We aim to understand the molecular mechanisms of glucose metabolism and response to fasting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 41 publications
5
12
1
Order By: Relevance
“…DBC1 serves as an endogenous inhibitor HDAC3 [38], and it plays a crucial physiological role as a modulator of epigenetics and metabolic function. In an earlier study, DBC1 knockout mice showed increased expression of PEPCK and gluconeogenesis, whereas over expression DBC1 reduced the PEPCK expression [39]. As we saw a negative correlation between HDAC3 activity and mRNA levels of DBC1 in our study, it appears that the regulatory circuit of endogenous control of HDAC3 could be somehow lost in patients with type 2 diabetes and this needs to be studied in-depth in future investigations.…”
Section: Discussionsupporting
confidence: 53%
“…DBC1 serves as an endogenous inhibitor HDAC3 [38], and it plays a crucial physiological role as a modulator of epigenetics and metabolic function. In an earlier study, DBC1 knockout mice showed increased expression of PEPCK and gluconeogenesis, whereas over expression DBC1 reduced the PEPCK expression [39]. As we saw a negative correlation between HDAC3 activity and mRNA levels of DBC1 in our study, it appears that the regulatory circuit of endogenous control of HDAC3 could be somehow lost in patients with type 2 diabetes and this needs to be studied in-depth in future investigations.…”
Section: Discussionsupporting
confidence: 53%
“…In the latter model, female mice developed a “fit obese” phenotype, i.e., obesity with insulin sensitivity, and reduced adipocyte lipolysis (Escande et al, 2015). Neither in two previous reports (Escande et al, 2015; Nin et al, 2014), nor in our study are males protected from diet-induced insulin resistance, raising the possibility of sex-dimorphic actions of Dbc1. We did not observe protection from diet-induced steatosis on chow/HFD feeding (not shown) or through Scd1 inhibition (Figure S5), possibly due to different knockout strategies or experimental conditions.…”
Section: Discussioncontrasting
confidence: 99%
“…The metabolic abnormalities in our Dbc1 −/− mice are largely consistent with those in knockouts generated by genetrap methodology (Escande et al, 2010; Escande et al, 2015; Nin et al, 2014). In the latter model, female mice developed a “fit obese” phenotype, i.e., obesity with insulin sensitivity, and reduced adipocyte lipolysis (Escande et al, 2015).…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies demonstrated that DBC1 might modulate liver gluconeogenesis through binding and regulating Rev-erbα, SIRT1, and phosphoenolpyruvate carboxykinase (PEPCK) (Nin et al, 2014). The higher expression of DBC1 compared to DBC1a (Fig.8 c) showed that the DBC1 was the main isoform in liver.…”
Section: Discussionmentioning
confidence: 82%
“…The higher expression of DBC1 compared to DBC1a (Fig.8 c) showed that the DBC1 was the main isoform in liver. Overexpression of DBC1 decreases mRNA and protein levels of PEPCK, while DBC1 knockout mice displayed the converse result (Nin et al, 2014).…”
Section: Discussionmentioning
confidence: 98%